Modern Determinants of the Vocational Education - KIEŁBASA, Marzena; NOGA, Henryk; MIGO, Piotr (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2015)
New education goals, a new teaching content requires from a teacher applicationof other, also more active teaching methods, and from students requirea lot of commitment and increased independence.This paper shows selected conditions of vocational education, paying attentionto the needs of acquiring new skills and the need for classification of occupations.